Influence of sampling depth and post-sampling analysis time on the occurrence of coliforms and vibrio in water and shellfish - Sallema, • R E; Mtui, G Y S (Tanzania Journal of Science, 2021)
The bacteriological quality was examined at the water surface, 3 m depth and in the shellfish flesh, and the results were compared to other potential pathogenic indicator organisms. The study was conducted at Long Harbour (mussel farm), St. John's and Outer Cove sites of Newfoundland, Canada. Bacteriological analysis was carried out for samples taken at water depth and at 1, 6, 12 and 24 hours post-sampling. It was observed that the total and faecal coliform bacteria were significantly higher in the 3 m water depth samples than in the surface water samples (ANOVA, F = 59.41, 26.751, 9.82 (T.C); 46.41, 26.81, 10.72 (F.C); P <0.001). In addition, shellfish tissues had substantial amounts of coliform bacteria levels, which varied significantly with station and date of sampling (F = 128.21,37.42 (T.C); 1281, 37.42 (F.C); P <0.05). The higher levels reflect bioaccumulation. There were no correlations between estimates of total or faecal coliforms with potential pathogenic Vibrio groups. Furthermore, there were no significant differences in total and faecal coliforms among the post-sampling time intervals. The results suggest that sampling and bacteriological analysis of water and shellfish for quality control should consider both the water surface and depths proximal to the shellfish. Moreover, adoption of extended post-sampling time may lead to a more convenient and less costly approach to monitoring of bacteriological impact on the coastal marine environments.